A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education, 2020)
Research has indicated the importance of preservice teacher education programs that focus on fostering positive psychological aspects relevant to teaching in inclusive settings such as attitudes or self-efficacy. Previous research lacks theoretical underpinning and is limited due to methodological characteristics of the studies (e.g., no control group). Thus, the current study aimed to investigate the effects of different theoretically derived interventions (IG1: information-based cognitive intervention group; IG2: information-based and practical field experience intervention group) in comparison to a control group (CG) on changes in preservice teachers’ perspective on teaching inclusively, i.e., explicit, implicit attitudes; self-efficacy, stress perception, relevant to teach in inclusive settings. Results showed no differences in the development (pre to post intervention) between CG and IG1 as well as CG and IG2. Even though, significant differences in changes in explicit attitudes and stress perception were found between IG1 and IG2 in favor of IG2. Results will be discussed considering confounding variables that future research should further investigate.